Effect of dietary inclusion of lecithin with choline on physiological stress of serum cholesterol fractions and enzymes, abdominal fat, growth performance, and mortality parameters of broiler chickens. Issue 6 (11th November 2020) - Rahnama, Mostafa; Bouyeh, Mehrdad; Kadim, Isam; Seidavi, Alireza; Elghandour, Mona M. M. Y.; Reddy, Poonooru Ravi Kanth; Monroy, José Cedillo; Salem, Abdelfattah Z. M.
Abstract: A total of 270 one-d-old Ross 308 broiler chicks were randomly allotted to 9 experimental diets (3 replicates of 10 birds each), including three types of supplemental lipotropic factors (control, 0.1% or 0.2% choline and 0.5% or 1% lecithin) in a 3 × 3 factorial arrangement. Supplementation of lecithin improved FCR values during 1-21 days of age. Although no differences were noticed for mortality index among different diets, the group supplemented with a combination of choline (0.1) and lecithin (0.5) showed the highest ( P  < 0.0001) production index. Choline (0.1% or 0.2%) significantly decreased serum total cholesterol by 11%, triglycerides by 21%, low-density lipoprotein (LDL) by 20%, and very low-density lipoprotein (VLDL) by 20%, while increased the glucose and high-density lipoprotein (HDL) values by 11% and 6%, respectively. On the other hand, lecithin significantly increased glucose, total cholesterol, triglycerides, HDL, LDL and VLDL by 4%, 9%, 7%, 24%, and 25%, respectively. Choline supplementation decreased the aspartate amino transferase (AST), alanine amino transferase (ALT), and alkaline phosphatase (AP); however, the lecithin addition increased their respective proportions. This study concluded that the combinations of 0.1% choline and 0.5% lecithin is the best among all other treatments because of the highest production index and least mortality.